2014
DOI: 10.3389/fchem.2014.00106
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thermoelectric performance of SrSi2-based alloys via the modification in band structure and phonon-point-defect scattering

Abstract: Thermoelectric properties of alkaline-earth-metal disilicides are strongly dependent on their electronic band structure in the vicinity of the Fermi level. In particular, the strontium disilicide, SrSi2 with a narrow band gap of about few tens of meV is composed of non-toxic, naturally abundant elements, and its thermoelectric properties are very sensitive to the substitution/alloying with third elements. In this article, we summarize the thermoelectric performance of substituted and Sr-deficient/Sr-rich SrSi2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…In general, the major difficulty in obtaining good thermoelectric performance of materials is to enhance the power factor (P F = S 2 /ρ) while simultaneously reducing κ [38][39][40][41]. For Ru 1.95 Ta 1.05 Al, we found that the room-temperature κ is suppressed to about 3.8 W/mK, as indicated in Fig.…”
Section: A Electrical Transport and Thermoelectric Propertiesmentioning
confidence: 63%
“…In general, the major difficulty in obtaining good thermoelectric performance of materials is to enhance the power factor (P F = S 2 /ρ) while simultaneously reducing κ [38][39][40][41]. For Ru 1.95 Ta 1.05 Al, we found that the room-temperature κ is suppressed to about 3.8 W/mK, as indicated in Fig.…”
Section: A Electrical Transport and Thermoelectric Propertiesmentioning
confidence: 63%
“…The specific heat data for these SMAs were obtained using a high-resolution ac calorimeter with chopped light as a heat source. More details about these measurement techniques can be obtained elsewhere 25 28 , 38 . The presented electrical and thermal measurement systems are all equipped with a calibrated silicon diode thermometer (Lake Shore model DT-470-SD) and all data presented in the manuscript were recorded with a slow heating rate of about 20 K/h and reproducibility better than 2%.…”
Section: Methodsmentioning
confidence: 99%
“…The double-WSM state has been predicted recently in the inversion-asymmetric chiral compound strontium disilicide, SrSi 2 , through band structure calculations [44]. This is an interesting material because it is composed of non-toxic and naturally abundant elements, and it has been known for decades as a promising candidate for thermoelectric applications through chemical substitution [48][49][50][51][52][53]. The double-Weyl nodes in SrSi 2 are generated via a band inversion mechanism, and lie along the C 4 rotation axis as seen in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental situation with SrSi 2 , however, remain uncertain. Early transport measurements [53] reported SrSi 2 to be a narrow band gap (10 ∼ 30 meV) semiconductor, while more recent experiments find it to be a gapless semimetal [50,51]. Other experimental studies focusing on thermoelectric properties show that the semimetal state of SrSi 2 could be stabilized through chemical substitution of Sr by the lighter Ca atoms [50,51].…”
Section: Introductionmentioning
confidence: 99%